2016
DOI: 10.1177/0741932516657652
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Reading of an Early Intervention Program for Children at Risk of Learning Difficulties

Abstract: The study aimed to analyze the effects on reading of an early oral and written language intervention program for Spanish children at risk of learning difficulties. The goal of this classroom-based program was to prioritize a systematic approach to reading and writing and to foster phonological knowledge and the development of oral language (phonology, semantics, morphology, and syntax) within the Spanish school curriculum. The sample comprised 56 students at risk of learning difficulties. The repeated-measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
0
6
0
2
Order By: Relevance
“…Children with a normal intellectual level (PT ≥ 101 and E ≥ 5), but with reading, writing, or arithmetic scores below the 25th percentile, were considered to have specific LDs; these criteria have been used in previous studies and are in agreement with the recommended guidelines of the instrument used for the assessments (Fletcher, Coulter, Reschly, & Vaughn, ; García‐Vidal, González‐Manjón, & Ortiz, ; González‐Valenzuela & Martín‐Ruiz, ; Welsch, ). In other words, reading, writing, and mathematical performance were defined dichotomously as follows: LDs in reading, writing, or arithmetic if the child had a score below the 25th percentile in specific learning tests; no LDs in reading, writing, or arithmetic if the score was at the 25th percentile or above in each measure.…”
Section: Methodsmentioning
confidence: 99%
“…Children with a normal intellectual level (PT ≥ 101 and E ≥ 5), but with reading, writing, or arithmetic scores below the 25th percentile, were considered to have specific LDs; these criteria have been used in previous studies and are in agreement with the recommended guidelines of the instrument used for the assessments (Fletcher, Coulter, Reschly, & Vaughn, ; García‐Vidal, González‐Manjón, & Ortiz, ; González‐Valenzuela & Martín‐Ruiz, ; Welsch, ). In other words, reading, writing, and mathematical performance were defined dichotomously as follows: LDs in reading, writing, or arithmetic if the child had a score below the 25th percentile in specific learning tests; no LDs in reading, writing, or arithmetic if the score was at the 25th percentile or above in each measure.…”
Section: Methodsmentioning
confidence: 99%
“…Það er mikilvaegt fyrir margar sakir. Augljóst er að snemmtaek íhlutun getur komið í veg fyrir lestrarvanda og um leið minnkað líkurnar á þörf fyrir sérkennslu seinna meir (González-Valenzuela og Martín-Ruiz, 2017;Riley, 2006). Farsaelt lestrarnám frá upphafi gefur barninu meðbyr í námi og ýtir undir frekari velgengni í öðrum námsgreinum.…”
Section: Inngangurunclassified
“…• Strategies of self-regulated writing: self-correction, self-questions The effects of program application have been assessed in different studies; improvements were found in academic achievement, oral language, reading and writing in children with and without risk for presenting specific learning disabilities, from 4-to 7-years old, and a decrease in the percentage of these problems from 5-to 7-years old [68][69][70][71][72]. More research is needed to confirm whether these gains are maintained in the long term.…”
Section: Program For the Prevention Of Learning Disabilities In Readimentioning
confidence: 99%
“…The easiest activities are carried out between the ages of 4 and 5 years, with more complex activities at ages 6 and 7 [68][69][70][71]. • Drawing-word associations…”
Section: Program For the Prevention Of Learning Disabilities In Readimentioning
confidence: 99%
See 1 more Smart Citation